Pendampingan Orang Tua dalam Penggunaan Media Pembelajaran Daring Siswa Sekolah Dasar di Kelurahan Loa Buah - Annisa Qomariah; Indah Eka Pertiwi (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Today is online learning in Indonesia is a new thing in the world of education. The obstacle that often occurs is that educators have difficulty in determining the media that can be used according to online learning. Another problem is the lack of parental assistance. Therefore, the researchers provided assistance to parents in elementary school online learning by using learning media. The strategies and methods used by researchers are online and offline. The results of the mentoring process obtained from the use of learning media are learning interest, increased student motivation. However, this is not a solution to the problem of ineffective online learning. The implementation of parental assistance in using learning media for elementary school students in Loa Buah sub-district contains many factors, both in terms of supporting and inhibiting factors. Supporting factors are motivation, high interest and talent of students, family support, community and school. While the inhibiting factors are the lack of facilities or infrastructure used for online and offline learning, the lack of an internet network, not being able to buy quotas, the lack of student discipline during face-to-face mentoring, lack of discipline in using masks, and others.